Microglial Activation – Tuning and Pruning Adult Neurogenesis - Ekdahl, Christine T (Frontiers in Pharmacology, 2012)
Adult born neurons are encountering numerous choices during their development from neural stem cells to mature functionally integrated neurons in the brain. Microglia are part of the microenvironment within the neurogenic niches and possibly involved during the entire decision process. Mounting evidence suggest that microglia act as local equalizers capable of amplifying as well as filtering homeostatic signals. Depending on their state of activation, they may induce or facilitate different fundamental decisions in neurogenesis, such as proliferation or quiescence, cell survival or death, migration or establishment, growth or retraction of dendrites and axons, synaptic assembly or pruning, or tuning of synaptic transmission. Microglia are activated as a first line of defence against infections and participate in transforming the innate immunity into an adaptive immune response by recruiting systemic immune cells. So far, most studies have reported an acute decrease in the survival of new neurons following this classically activated microglial reaction. However, the long-term effects are more complex. In several neurodegenerative diseases the microglial activation is also evident, including a heterogeneous population of microglial phenotypes and a plethora of immune mediators, where the initiating agent may be protein deposits or cell debris. The transformation from a pro- to an anti-inflammatory cytokine profile and the de-activation of microglia is not clearly defined, or even dysregulated, and the adaptive response is often sparse. The diverse role of microglial activation in neurodegenerative diseases is reflected by the numerous studies reporting both beneficial and detrimental effects on the different steps of neurogenesis. This review will highlight the most recent findings on how microglial activation modulates adult neurogenesis, and specifically discuss the role of microglia in synaptic integration, currently a fast expanding research field.